Методи оцінки ефективності режимів світлофорного регулювання - Швець, Богдан; Давосир, Владислав; Криса, Марія (Видавництво Львівської політехніки, 2018)
Effectiveness of traffic light control regimes is evaluating by criteria of minimization of traffic participants delays and traffic safety indicators. By the first criterion must be achieved rational regulation regime for the purpose of movement delay balancing depending on need (intensity of transport and pedestrian flows), by the second – minimal amount of conflict points and directions on regulated facility.
Methods for evaluating the effectiveness of traffic light control regimes
Keywords: 656.11